Georgia Architectural and Historic Properties Survey of Brown Ave. [2], Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Brown Ave. [2], Sycamore, Turner County, Ga., 1981. Bungalow house with gabled roof. Gabled porch with square posts. Asbestos shingle siding. Double sash windows with 2/2 lights. Brick piers. Good condition. Date of Construction: c. 1925. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Brown Ave. [2], Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 55.6 MB (58,353,061 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)